CONDITIONS AND ATMOSPHERE OF ISLAMIC EFFECTIVE LEARNING - Wirian, Oktrigana; Agustina, Nelly (Proceeding International Seminar of Islamic Studies, 2023)
The effectiveness of the Islamic learning process is influenced by the environment, learning materials, educators, learning strategies, media and social background of students. In general In the process of Islamic education there are still many problems that are the target of education Islam, namely the awareness of students to practice Islamic law, faith, piety and morality noble in the process of life has not reached its target. Education provides sensibility assistance students in such a way that in their pattern of life they are able to take steps and decision-making, as well as their approach to science regulated in a very deep Islamic ethics. The learning process is an activity for teach students. To educate students, various equipment is needed including the selection, determination and development of methods based on conditions existing learning. The learning process can help students obtain information, ideas, skills, values, ways of thinking, means of self-expression of students and ways Study.